1988
DOI: 10.1143/jjap.27.169
|View full text |Cite
|
Sign up to set email alerts
|

Migration-Enhanced Epitaxy of GaAs and AlGaAs

Abstract: Surface migration is effectively enhanced by evaporating Ga or Al atoms onto a clean GaAs surface under an As-free or low As pressure atmosphere. This characteristic was utilized by alternately supplying Ga and/or Al and AS4 to the substrate surface for growing atomically-flat GaAs-AlGaAs heterointerfaces, and also for growing high-quality GaAs and AlGaAs layers at very low substrate temperatures. The migration characteristics of surface adatoms have been investigated through reflection hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
83
1

Year Published

1990
1990
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 364 publications
(88 citation statements)
references
References 20 publications
2
83
1
Order By: Relevance
“…The 4 nm AlN barriers were grown using migration enhanced epitaxy (MEE) [23] to ensure a smooth heterointerface between AlN and GaN by avoiding excess Al.…”
mentioning
confidence: 99%
“…The 4 nm AlN barriers were grown using migration enhanced epitaxy (MEE) [23] to ensure a smooth heterointerface between AlN and GaN by avoiding excess Al.…”
mentioning
confidence: 99%
“…Methods used have included growth on vicinal surfaces to ensure step-flow growth; growth interruption to allow surfaces to anneal; and various photon and ionised particle irradiation techniques which provide energy to enhance surface migration. A simple and effective technique was recently invented (Horikoshi et al 1988) which greatly enhances the surface mobility at At Tc the migration length is of order of the step separation (after Dobson et al 1987).…”
Section: Migration Enhanced Epitaxymentioning
confidence: 99%
“…11) where Ns is deduced from the three dimensional crystallography. But also as NGa is increased, maxima in the oscillation recovery occur at NGa = 2Ns and 3Ns: it is thought that the excess Ga atoms form droplets which act as a source for two dimensional growth when the As is deposited (Horikoshi et al 1989). These droplets have been observed in RHEED images (Yamada et al 1989).…”
Section: Migration Enhanced Epitaxymentioning
confidence: 99%
“…However, HVPE of AlN has proved successful using AlCl3, which does not react with the quartz reactor at the growth temperatures [1]. In addition, we have reported that AlGaN ternary alloy can be grown by HVPE using GaCl-AlCl3-NH3 system [2]. In the presentation, a thermodynamic analysis of the HVPE of AlN using AlCl3 and AlGaN using AlCl3 and C87 Quantum dots (QDs) of nitride semiconductors have been studied intensively because of their usefulness for device applications.…”
mentioning
confidence: 99%
“…The time sequence of the opening of the shutter of a Ga effusion cell was used for the trigger signal to operate the mode change operation of nitrogen ICP -RF discharge. An activity modulation migration enhanced epitaxial growth (AM-MEE) method is prpposed as an application of the MEE [2]. In order to grow the high quality layers on a Si substrate the AM-MEE growth method was performed.…”
mentioning
confidence: 99%